Frequency of Staphylococcus Aureus Infection Associated with Femoral Double Lumen Catheter in Kidney Failure Patients - Ihtisham Khan, Muhammad Faizan, Wafa Naeem, Muhammad Zubair, Ahmad Shamim Khan, Syed Luqman Shuaib, Sadir Zaman, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The most frequent pathogens responsible for renal failure in hospitalised patients are Staphylococcus species, particularly in those receiving hemodialysis. The aim was to isolate and identified the Staphylococcus species from hemodialysis patients. Methodology: The research was carried out between November 2021 and February 2022. This study included participants who were receiving maintenance hemodialysis for end-stage renal illness. Each patient's demographic information was gathered using a structured questionnaire that had been evaluated beforehand. Blood samples from both sexes were taken (28 males and 22 females). The blood samples were sent directly to the research lab for processing after being inoculated into the Brain Heart Infusion broth under aseptic circumstances. Gram stain and biochemical assays were used to determine the bacteria's identity. Result :Overall, there were 44 percent female patients and 56 percent male patients. Out of all the blood samples analyse, 26% of samples showed evidence of bacterial development in the Brain Heart Infusion broth. S. aureus species (62 percent), S. epidermidis (15 percent), and S. saprophyticus were the Staphylococcus species that were detected 23 percent). Conclusion According to the findings, coagulase-positive Staphylococci were the most often isolated species from hemodialysis patients who had bacteremia, but coagulase-negative strains were identified far less frequently. The findings of the current study need to be confirmed by more research.